Cholecystectomy for Biliary Hyperkinesia. Issue 2 (February 2019) - Gazzetta, Joshua; Fan, Betty; Bonner, Paul; Galante, John
Patients with classic biliary colic symptoms and documented gallbladder ejection fractions on the higher end of the spectrum on hepatobiliary iminoacetic acid scans with cholecystokinin stimulation are presently understudied and the benefits of cholecystectomy are unclear. To determine whether patients with biliary-type pain and biliary hyperkinesia (defined as a gallbladder ejection fractions of 80% or greater) benefit from laparoscopic cholecystectomy, a retrospective chart review encompassing five community hospitals was performed. Patients 16 years and older with diagnosed biliary hyperkinesia who underwent laparoscopic cholecystectomy between January 1, 2010 and May 31, 2015 were included. Pathology reports were reviewed for histologic changes indicating cholecystitis. Resolution of biliary colic symptoms was reviewed one to three weeks after surgery in their postoperative follow-up documentation. Within our study cohort, we found 97 patients who underwent laparoscopic cholecystectomy for biliary hyperkinesia. Within this population, 84.5 per cent of patients undergoing laparoscopic cholecystectomy for biliary hyper-kinesia had positive findings for gallbladder disease on final pathology. Of the 77 patients with data available from their first postoperative visit, 70 (90.9%) reported improvement or resolution of symptoms. Our findings suggest that symptomatic biliary hyperkinesia may be treated successfully with surgery.